Confirmatory Factor Analysis of the School-Based Assessment Evaluation Scale Among Teachers - Nor Hasnida Che Md. Ghazali (Ta'dib: Jurnal Pendidikan Islam, 2016)
The school-based assessment (SBA) system is a holistic assessment system that is conducted in schools by subject teachers in assessing the students cognitive (intellect), affective (emotional and spiritual) and psychomotor (physical) aspects. It is in line with the National Philosophy of Education and the Standards-based School Curriculum in Malaysia. In order to evaluate the implementation of SBA, a measurement scale was validated. Questionnaire was used as an instrument for data collection. 776 primary and secondary school teachers were selected as respondents using stratified random sampling. The data was analyzed with SPSS and AMOS version 18. The aim of this paper was to explore different factor structures of the SBA evaluation scale by using the second-order Confirmatory Factor Analysis. Results indicated that the SBA evaluation model was a valid and reliable scale. The input measurement model was validated with two factors (personnel qualifications and physical infrastructure), process measurement model was validated with six factors (‘attitude’, ‘understanding’, ‘skills’, ‘challenges’, ‘moderation’ and ‘monitoring’) and product measurement model was validated with two factors (‘students’ attitude’ and ‘students’ motivation’). This study provides support for using a valid instrument in evaluating the implementation of SBA in schools. Furthermore, the CFA procedures used supported the conceptual framework set out earlier. Thus, it presents clearly the importance of the evaluation process of any education system to follow all the dimensions outlined in the evaluation model proposed by Daniel Stufflebeam.     Sistem Penilaian Berbasis Sekolah (SBA) adalah sistem penilaian holistik yang dilakukan di sekolah-sekolah oleh guru mata pelajaran dalam menilai kognitif (kecerdasan), afektif (emosional dan spiritual) dan psikomotorik (fisik) siswa. Hal ini sejalan dengan Filsafat Pendidikan Nasional dan Kurikulum Sekolah Berbasis Standar di Malaysia. Dalam rangka untuk mengevaluasi pelaksanaan SBA, skala pengukuran divalidasi. Kuesioner digunakan sebagai instrumen untuk pengumpulan data. Tujuh ratus tujuh puluh enam guru sekolah dasar dan menengah terpilih sebagai responden dengan menggunakan Stratified Random Sampling. Data dianalisis dengan SPSS dan AMOS versi 18. Tujuan dari makalah ini adalah untuk mengeksplorasi struktur faktor yang berbeda dari skala evaluasi SBA dengan menggunakan Confirmatory Factor Analysis. Hasil penelitian menunjukkan bahwa model evaluasi SBA merupakan skala yang valid dan reliabel. Model pengukuran masukan divalidasi dengan dua faktor (kualifikasi personil dan infrastruktur fisik), model pengukuran proses telah divalidasi dengan enam faktor (sikap, pemahaman, keterampilan, tantangan, moderasi dan pemantauan) dan model pengukuran produk divalidasi dengan dua faktor (sikap dan motivasi siswa). Studi ini memberikan masukan untuk menggunakan alat yang sah dalam mengevaluasi pelaksanaan SBA di sekolah-sekolah. Selain itu, prosedur CFA digunakan mendukung kerangka kerja konseptual yang ditetapkan sebelumnya. Dengan demikian, menyajikan dengan jelas pentingnya proses evaluasi dari setiap sistem pendidikan untuk mengikuti semua dimensi yang digariskan dalam model evaluasi yang diusulkan oleh Daniel Stufflebeam.